Market Reforms and Efficiency Gains in Chile - Bergoeing, Raphael; Hernando, Andrés; Repetto, Andrea (Estudios de Economía, 2016)
Starting in the mid 1970s, Chile implemented comprehensive structural market reforms. Using manufacturing plant-level data on Chilean firms for years 1980 to 2001, we estimate the role of reforms on efficiency. We analyze aggregate productivity constructed from micro data to find that in the aftermath of the reforms, efficiency gains were explained by within-plant improvements andby the net entry of new units. We also find that plants producing traded goods and plants facing liquidity constraints experienced the largest efficiency gains. Trade openness and a superior access to external finance seem to have partially accounted for the improvement in manufacturing performance.